Decorating homes on Narli Purnima - Mumbai Archive Project Team (Jio Institute, 2024)
To mark the auspicious occasion of Narli Purnima, Koli homes are cleaned, painted, and decorated with toran (floral garlands) hung over the entrances. Some households also make colourful rangoli (decorative patterns) at the entrance.